Force–displacement measurements of earlywood bordered pits using a mesomechanical tester. (29th April 2015) - Zelinka, Samuel L.; Bourne, Keith J.; Hermanson, John C.; Glass, Samuel V.; Costa, Adriana; Wiedenhoeft, Alex C.
Abstract The elastic properties of pit membranes are reported to have important implications in understanding air‐seeding phenomena in gymnosperms, and pit aspiration plays a large role in wood technological applications such as wood drying and preservative treatment. Here we present force–displacement measurements for pit membranes of circular bordered pits, collected on a mesomechanical testing system. The system consists of a quartz microprobe attached to a microforce sensor that is positioned and advanced with a micromanipulator mounted on an inverted microscope. Membrane displacement is measured from digital image analysis. Unaspirated pits from earlywood of never‐dried wood of Larix and Pinus and aspirated pits from earlywood of dried wood of Larix were tested to generate force–displacement curves up to the point of membrane failure. Two failure modes were observed: rupture or tearing of the pit membrane by the microprobe tip, and the stretching of the pit membrane until the torus was forced out of the pit chamber through the pit aperture without rupture, a condition we refer to as torus prolapse.